Enzymatic activity of a novel halotolerant lipase from Haloarcula hispanica 2TK2 - BİRBİR, MERAL (DE GRUYTER POLAND SP ZOO, 2016)
A strain of Haloarcula hispanica isolated from Tuzkoy salt mine, Turkey exhibited extracellular lipolytic activity. Important parameters such as carbon sources and salt concentration for lipase production were investigated. Optimal conditions for the enzyme production from Haloarcula hispanica 2TK2 were determined. It was observed that the lipolytic activity of Haloarcula hispanica was stimulated by some of the carbon sources. The high lipase acitivity values were obtained in the presence of 2% (v/v) walnut oil (6.16 U/ml), 1% (v/v) fish oil (5.07 U/ml), 1% (v/v) olive oil (4.52 U/ml) and 1% (w/v) stearic acid (4.88 U/ml) at 4M NaCl concentration. Lipase was partially purified by ammonium sulfate precipitation and ultrafiltration. Optimal temperature and pH values were determined as 45 degrees C and 8.0, respectively. Lipase activity decreased with the increasing salt concentration, but 85% activity of the enzyme was maintained at 5M NaCl concentration. The enzyme preserved 41% of its relative activity at 90 degrees C. The partially purified lipase maintained its activity in the presence of surfactants such as Triton X-100 and SDS. Therefore, the lipase which is an extremozyme may have potential applications especially in detergent industry.
Keywords: Haloarcula hispanica; extremely halophilic archaea; extremozyme; lipase; lipolytic activity; BIOCHEMICAL-CHARACTERIZATION; EXTRACELLULAR LIPASE; GEOTRICHUM-CANDIDUM; LIPOLYTIC-ACTIVITY; PURIFICATION; EXTREMOPHILES; EXTREMOZYMES; MARISMORTUI; ESTERASE; ASSAY